PENERAPAN PENDEKATAN STEAM BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KREATIVITAS DAN LITERASI SAINS SISWA SEKOLAH DASAR - Ria Farida; Haifaturrahmah; Nursina Sari (STKIP Subang, 2025)
This study aims to describe the implementation of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach based on local wisdom to enhance elementary students’ creativity and scientific literacy. The research employed a descriptive qualitative approach involving one fourth-grade teacher and 25 students at SDN 3 Karang Bongkot, selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results indicate that integrating STEAM with local wisdom significantly improves students’ engagement, creativity, and scientific literacy. Students became more enthusiastic in connecting scientific concepts with local culture through contextual projects combining art and simple technology. Moreover, this approach fostered essential character values such as collaboration, responsibility, and appreciation for local traditions. Therefore, the STEAM-based local wisdom approach is proven to be an effective and innovative learning strategy for elementary education. Keywords: STEAM, local wisdom, creativity, scientific literacy, elementary education